Effect of Low Ambient Pressure on Spray Cone Angle of Pressure Swirl Atomizer - Zhengyan Guo; Yi Jin; Kai Zhang; Kanghong Yao; Yunbiao Wang; Di Wu; Xiaomin He; Mei Zheng (International Journal of Aerospace Engineering)
Pressure swirl atomizers are widely used in gas turbine combustor; this paper is aimed at researching the effect of low ambient pressure (0.1 MPa to 0.01 MPa, lower than an atmosphere) on the spray cone angle of pressure swirl atomizer. The spray angle is captured by high-speed photography; then, an image post program is used to process the spray angle magnitude. A mathematical model of a single droplet’s movement and trajectory based on force analysis is proposed to validate the spray angle variation. The maximum variation of the spray cone angle, which is observed when fuel supply pressure drop through the atomizer is 1 MPa as the ambient pressure decreases from 0.1 MPa to 0.01 MPa, is found to be 23.9%. The experimental results show that the spray cone angle is expected to increase with the ambient pressure decrease; meanwhile, mathematical results agree well with this trend.